Notes for a History of the Hospital de San Andrés. Salta (Argentina). First Half of the XIX Century - Enrique Quinteros, Víctor (2022)
The aim of this article is to reconstruct the course of the Hospital de San Andrés in the city of Salta, administered by the order of the Betlemitas during the first half of the 19th century, in order to outline the guidelines of the nosocomial project implemented and, through this, to address the relations forged between civil and ecclesiastical powers in the period of transition from one order to another. We work mainly with various provisions implemented, first, by the colonial authorities in the framework of the reform program promoted by the Bourbons; second, by the revolutionary and independent governments. The proposed study will allow us to expose some particular characteristics and trajectories of the secularization process in the city of Salta.